3D Synergistically Active Carbon Nanofibers for Improved Oxygen Evolution. Issue 14 (17th March 2017) - Zhu, Yun Pei; Jing, Yu; Vasileff, Anthony; Heine, Thomas; Qiao, Shi‐Zhang
Abstract : Developing earth‐abundant and active electrocatalysts for the oxygen evolution reaction (OER) as replacements for conventional noble metal catalysts is of scientific and technological importance for achieving cost‐effective and efficient conversion and storage of renewable energy. However, most of the promising candidates thus far are exclusively metal‐based catalysts, which are disadvantaged by relatively restricted electron mobility, corrosion susceptibility, and detrimental environmental influences. Herein, hierarchically porous nitrogen (N) and phosphorus (P) codoped carbon nanofibers directly grown on conductive carbon paper are prepared through an electrochemically induced polymerization process in the presence of aniline monomer and phosphonic acid. The resultant material exhibits robust stability (little activity attenuation after 12 h continuous operation) and high activity with low overpotential (310 mV at 10 mA cm −2 ) toward electrocatalytic oxygen production, with performance comparable to that of the precious iridium oxide (IrO2 ) benchmark. Experimental measurements reveal that dual doping of N and P can result in an increased active surface area and abundant active sites in comparison with the single doped and pristine carbon counterparts, and density functional theory calculations indicate that N and P dopants can coactivate the adjacent C atoms, inducing synergistically enhanced activity toward OER. Abstract : 3D carbon electrocatalysts: highly porous nitrogen and phosphorus codoped carbon nanofibers, prepared through the pyrolysis of polyaniline synthesized in the presence of phosphonic acid, are rationally designed to show outstanding electrocatalytic oxygen evolution performance. Electrochemical measurements in combination with density functional theory simulations reveal a synergistic effect from the dual‐doped heteroatoms in boosting electrochemical activity.